Register to reply

Why negative times negative is positive

by gurudon
Tags: negative, positive, times
Share this thread:
gurudon
#1
Feb24-12, 10:34 AM
P: 8
hey friend can anybody give answer?
why (-) * (-) = (+)
Phys.Org News Partner Mathematics news on Phys.org
'Moral victories' might spare you from losing again
Fair cake cutting gets its own algorithm
Effort to model Facebook yields key to famous math problem (and a prize)
HallsofIvy
#2
Feb24-12, 11:09 AM
Math
Emeritus
Sci Advisor
Thanks
PF Gold
P: 39,304
Its impossible to give an explanation that you would accept without knowing what kind of explanation you would accept!

For example, one can show that a(b+ c)= ab+ ac (the "distributive law"). In particular, if we take a=-x, b=y, c= -y, that says -x(y+ (-y))= -x(y)+ (-x)(-y). But y+(-y)= 0 and -x(0)= 0 so that tells us that -x(y)+ (-x)(-y)= 0. Adding x(y) to both sides, -x(-y)= x(y).

Is that acceptable?
dx
#3
Feb24-12, 11:16 AM
HW Helper
PF Gold
dx's Avatar
P: 1,961
Think of -a as a reflection of a through the origin. Reflecting twice gives you back a: -(-a) = a.

gurudon
#4
Feb25-12, 10:42 AM
P: 8
Why negative times negative is positive

i was cleared after going through this.
http://www.mathsisfun.com/multiplying-negatives.html
daveyinaz
#5
Feb25-12, 11:09 AM
P: 225


nice link
vkash
#6
Feb26-12, 04:51 AM
P: 318
I have a simple explanation if u confined to Integers only
first of u need to know why - * + = -
multiplication is seemed to be derived from addition. Like2*3=2+2+2. and 3+4=3+3+3+3..
So when u write (-3)*4= (-3)+ (-3)+ (-3)+ (-3)=- (-12)
hence it is proved that (-)* (+)= (-)

Now come to (-)* (-)= (+)
Let me say u want to solve the question something like this. (-1)/1. you must have done divisions in primary classes where you make make a pie ∏ shape. write denominator part inside and numerator part outside etc,..
when u do such ting with (-1)/1. then u have two choices for quotient 1 or (-1). If u put 1 then using quotient rule. 1*(-1)+0=1 . But it's wrong so -1 is only answer u can think of..

All this is poor explanation since real numbers and complex number are not taken.
Quote Quote by Hallsoflvy
Its impossible to give an explanation that you would accept without knowing what kind of explanation you would accept!

For example, one can show that a(b+ c)= ab+ ac (the "distributive law"). In particular, if we take a=-x, b=y, c= -y, that says -x(y+ (-y))= -x(y)+ (-x)(-y). But y+(-y)= 0 and -x(0)= 0 so that tells us that -x(y)+ (-x)(-y)= 0. Adding x(y) to both sides, -x(-y)= x(y).

Is that acceptable?
these all are based on logics and data.2+(3+5)=2*8=2*3+2*5 after many tries it was found that is applicable everywhere so it's made as property of numbers.
similar about others...
awkward
#7
Feb26-12, 09:02 AM
P: 327
There are several good explanations here:

http://mathforum.org/dr.math/faq/faq.negxneg.html
gurudon
#8
Feb29-12, 12:12 AM
P: 8
mathforum is also not bad..


Register to reply

Related Discussions
Is zero positive or negative ? General Math 112
Negative times negative General Math 9
Neither positive nor negative ? General Math 85
Component vectors positive or negative and angles positive or negative Introductory Physics Homework 5
Why a negative times a negative is positive General Math 0